Cytomegalovirus non-primary infection during pregnancy. Can serology help with diagnosis?. (17th January 2017) - Picone, O.; Grangeot-Keros, L.; Senat, Mv; Fuchs, F.; Bouthry, E.; Ayoubi, Jm; Benachi, A.; Vauloup-Fellous, C.
Abstract: Diagnosis of cytomegalovirus (CMV) primary infection is reliable, but diagnosis of CMV non-primary infection (NPI) is questionable. Our aim is to highlight the difficulties met in diagnosis of CMV NPI. We illustrate that in proven cases of CMV NPI, very different serologic and molecular patterns may be observed and that routine serologic testing may fail to help with diagnosis. These results point out that many data available in literature concerning the prevalence of NPI, materno-fetal transmission rates and consequences of NPI may be wrong. We need to know how frequently they occur, are transmitted and cause fetal damages. Diagnosis of NPI must be improved, along with our understanding of the mechanisms leading to intrauterine CMV transmission and congenital infection in babies born to women with preexisting immunity.